THE ROLE OF ARTIFICIAL INTELLIGENCE TOOLS IN THE MODULAR STRUCTURE OF A FOREIGN LANGUAGE TEACHING PLATFORM BASED ON COGNITIVE AND CONSTRUCTIVIST APPROACHES (GENERATIVE AI, NLP): https://doi.org/10.5281/zenodo.20432350 - Turakulov , Olim; Abdumalikov , Akmaljon; Kayumov , Oybek; Aliyeva , Raykhona; Yo’ldosheva , Madina (Scientific practical conference, 2026)
This article develops a modular architecture of a foreign language teaching platform based on cognitive and constructivist approaches. The proposed model consists of basic and auxiliary modules. The functional role of generative artificial intelligence and natural language processing tools is analyzed.